CHANGES IN THE LEVEL OF DEVELOPMENT OF RURAL AREAS IN POLAND AFTER ITS ACCESSION TO THE EUROPEAN UNION – RESULTS OF COMMUNE CATEGORISATION - Grażyna Adamczyk-Łojewska; Adam Bujarkiewicz (Acta Scientiarum Polonorum. Oeconomia, 2018)
The aim of the paper was to present the analysis and evaluation of economic development in rural areas in Poland within a 10-year span between 2003 and 2012, i.e. in conditions of deepening integration process, when the Cohesion Policy was being implemented after accession to the European Union. The paper presents the results of research conducted by the authors across the entire country at the level of communes that employed Regional Data Banks (RDBs) of the Central Statistical Office (GUS) and GIS techniques. Allowing for comparable criteria covering eight analysed factors, relative level of development in individual communes – high, medium or low (category A, B or C, respectively) – was determined independently for four years (2003, 2008, 2010, and 2012). Then it was used as a basis for delimitation (on the national and provincial level) of areas varying in terms of the level of development (A, B and C) independent for each of these four years, and as a basis for identifying alterations in the area and population ranges in areas belonging to particular categories and their locations within the studied 10-year period.